Community Responsiveness on Climate Change and Natural Hazards Towards Sustainable Cities: An Empirical Study of Da Nang, Vietnam - Toan, Nguyen Duc (VNU Journal of Science: Earth and Environmental Sciences; Vol 40 No 2DO - 10.25073/2588-1094/vnuees.5121, 2024)
Understanding of community responsiveness on climate change and the natural hazards is an essential component of urban planning and adaptation strategies. The coastal cities are seriously affected by the impact of rising sea levels and climate change-induced hazards. In this paper, we investigate the urbanization level on climate change and natural hazards awareness of local communities at the households’ level in Da Nang city, the largest municipality in Central Vietnam using 1903 surveyed households. The results showed that the urbanization level significantly influenced the local communities' responsiveness to climate change. Communities with robust infrastructure and strong economic status demonstrate greater resilience and awareness of climate change and natural hazards compared to others. Therefore, it is recommended to prioritize enhancing local people’s responsiveness to develop bottom-up climate change response strategies and policies, instead of enforcing top-down decisions.